STUDENTS' STRATEGIES AND ERRORS IN JOURNALISTIC TEXT TRANSLATION - Asi, Natalina; Fauzan, Akhmad; Nugraha, Richard Ferry; Binti, Jeremy Audra Yoal Putra; Vanesa, Naftali (STKIP Persada Khatulistiwa Sintang, 2024)
Journalistic text plays an important role in information transfer such as the latest events, issues, or problems from parts of the world. With the rapid development of digital platforms, journalistic can be accessed easily through the internet, which arouses the need for translation as a means to bridge understanding between languages. Therefore, this study aimed to investigate students’ strategies and errors in journalistic text translation. By referring to translation strategies adapted from Newmark (1988), Hoed (2006), Baker (2011), the target text was analyzed based on several strategies including transference, calque, naturalization, accepted translation, paraphrase, modulation, transposition, cultural equivalence, addition, omission, and explication. Based on the translation quality assessment model adapted from Nababan et al. (2012), the translations made by the students have decent quality for accuracy and a medium level of competence in producing acceptable translations. However, the translation products have a high degree of readability which means they are easy to understand. Based on the classification proposed by Sukur et al. (2020), the finding shows that the errors made by the students in translating journalistic texts include a lack of cultural background knowledge, situation concordance, use of unsuitable words to the context, and failure to understand speech act. With some suggestions to overcome those challenges, this study is expected to provide pedagogical insight for translation courses regarding the practice of journalistic translation.